2020
DOI: 10.3139/104.112326
|View full text |Cite
|
Sign up to set email alerts
|

Digitaler Zwilling des Produktionssystems

Abstract: Kurzfassung Ein Digitaler Zwilling eines Produktionssystems kann vielfältig zur Planung, Steuerung und Optimierung genutzt werden. Bislang sind seine Erstellung und Pflege jedoch noch sehr aufwändig, weshalb häufig nicht der reale Zustand der Produktion abgebildet ist bzw. schnell veraltet und der Digitale Zwilling somit nicht mehr effektiv genutzt werden kann. Dieser Beitrag präsentiert ein Konzept für Digitale Zwillinge von Produktionssystemen, die sich selbstständig an die reale Produktion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On the one hand, the required knowledge to create or operate a simulation is often missing. On the other hand, many simulation tools are far too complex and not user-friendly, and the creation of a specific simulation usually requires much time, capacity, and know-how [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the required knowledge to create or operate a simulation is often missing. On the other hand, many simulation tools are far too complex and not user-friendly, and the creation of a specific simulation usually requires much time, capacity, and know-how [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Trumpf Group offers manufacturing solutions in the fields of machine tools, laser technology, electronics, and power tools [11]. Simulation service providers cooperate with such large companies because creating, operating, and inevitably maintaining such a simulation requires a high level of knowledge on this subject [4]. During the literature review, no proof could be found that small-and medium-sized enterprises (SME) use simulations in their daily production routine.…”
Section: Introductionmentioning
confidence: 99%